Social Media as a Health Promotion Tool: Between Education and Misinformation - Theresia N.A Narwadan; Seno Lamsir (Journal of Public Health Indonesian, 2025)
Social media has become a central instrument for health promotion in Indonesia, yet it simultaneously serves as a fertile environment for health-related disinformation. This study provides a comprehensive analysis of how social media functions in these dual roles both as a tool for health education and a channel for misinformation using a mixed-method integrative review approach. A total of 62 eligible articles were analyzed using thematic synthesis integrating quantitative and qualitative findings. The results reveal that social media can enhance the reach of health education through multimodal content, personalized messaging, and community engagement. However, engagement-driven algorithms, low digital health literacy, and the influence of non-expert figures enable disinformation to spread more rapidly than accurate information. These dynamics highlight the necessity for systemic interventions, including stronger information governance, improved health literacy programs, collaborations with content creators, and platform-level reforms that reduce the visibility of misleading content. The study concludes that social media can only function effectively as a health promotion tool if its educational potential is balanced with comprehensive and contextually grounded strategies to mitigate disinformation.